Corporate financing choices after the 2007-2008 financial crisis - Pinto, João M. (2018)
We study the factors that, arguably, affect the probability of a new borrower choosing between structured finance (SF), either project finance (PF) loans or asset securitization (AS) bonds, and straight debt finance (SDF) – corporate bonds (CB) – transactions using a large cross section of 24,435 Western European loans and bonds issued between January 1st, 2000 and December 31st, 2011. Borrowers chose an SF transaction when they seek long-term financing and when they operate in a country with lower sovereign rating. Findings suggest that industrials, utilities, transportation, and governmental borrowers exhibit a higher likelihood of an SF transaction, more specifically, a PF transaction. Several macroeconomic factors, like market interest rate levels and volatility, and the slope of the Euro swap curve, positively influence the probability of observing an SF over an SDF transaction. The 2007-2008 financial crisis and the subsequent European sovereign debt crisis decrease the probability of observing an AS transaction. During the crisis, macroeconomic factors seem to significantly influence the probability of a sponsor to choose SF over SDF. We also find that credit spreads and loan to value ratios have a significant negative relationship for AS bonds. Overall, findings are in line with security design literature. SF transactions or instruments, based on extensively contractual and security design, allow the reduction of the net costs associated with asymmetric information and agency conflicts.